ОНКОЛОГИК БЕМОРЛАРДА КАСАЛЛИКНИНГ ИЖТИМОИЙ ТАЪСИРИНИ СУБЪЕКТИВ БАҲОЛАШ МАСАЛАСИНИНГ МУҲИМЛИГИ - Уразбаева, Д.А. (SCIENCE and SOCIETY, 2019)
In the article the author analyzed the problem of the need for an experimental study of the subjective characteristics of the social influence on cancer patients.